2023
DOI: 10.1038/s41467-023-35945-y
|View full text |Cite
|
Sign up to set email alerts
|

ViralCC retrieves complete viral genomes and virus-host pairs from metagenomic Hi-C data

Abstract: The introduction of high-throughput chromosome conformation capture (Hi-C) into metagenomics enables reconstructing high-quality metagenome-assembled genomes (MAGs) from microbial communities. Despite recent advances in recovering eukaryotic, bacterial, and archaeal genomes using Hi-C contact maps, few of Hi-C-based methods are designed to retrieve viral genomes. Here we introduce ViralCC, a publicly available tool to recover complete viral genomes and detect virus-host pairs using Hi-C data. Compared to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The electron transfer between Ag and Cu may lead to the formation of Ag-Cu bonds, as well as the existence of an Ag-Cu interface. 42 Accordingly, the Cu K-edge analysis presented a slightly higher valence state of Cu than that of the Cu 2 O reference. Moreover, the k 2 -weighted Ag K-edge EXAFS showed that the bond length and coordination number of Ag in Ag/Cu/ Cu 2 O Ag 0.1 HKUST-1 were slightly reduced, suggesting the formation of a heterostructure rather than alloys.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The electron transfer between Ag and Cu may lead to the formation of Ag-Cu bonds, as well as the existence of an Ag-Cu interface. 42 Accordingly, the Cu K-edge analysis presented a slightly higher valence state of Cu than that of the Cu 2 O reference. Moreover, the k 2 -weighted Ag K-edge EXAFS showed that the bond length and coordination number of Ag in Ag/Cu/ Cu 2 O Ag 0.1 HKUST-1 were slightly reduced, suggesting the formation of a heterostructure rather than alloys.…”
Section: Resultsmentioning
confidence: 86%
“…An AgCu single-atom alloy blended with Ag nanoparticles showed a 94 ± 4% FE towards multicarbon products at a high current density of ∼720 mA cm −2 in a ow cell, but the FE of C 2 H 4 was below 40%. 42 In contrast, Ag/ Cu/Cu 2 O Ag 0.1 /HKUST-1 can achieve the superiority of C 2 H 4 FE (∼50%), current output (>180 mA cm −2 ), and stability (600 min) at the same time, underscoring its promise for practical use. When a membrane electrode assembly (MEA) reactor is rationally designed for such restructured catalysts, we believe greater advances in performance, in particular the greater current density and long-term stability, can be accomplished.…”
Section: Resultsmentioning
confidence: 99%
“…Single-cell genomics can address the limitations of conventional metagenomics, which struggles to detect ARGs within plasmids and phages. While some cutting-edge research aims to connect MAGs, MGEs, and ARGs using Hi-C metagenomics, the extensive sequence reads required often limit MGE and ARG detection [43][44][45][46][47] . Single-cell genomics, with its ability to overcome such challenges, offers a refined view of the complex dynamics among ARGs, MGEs, and their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bioinformatic approaches, proximity ligation information (e.g., Hi-C) can also be used to bin contigs (Burton et al 2014;Press et al 2017;DeMaere & Darling 2019). The ProxiMeta platform (Press et al 2017), MetaCC (Du & Sun 2023), and metaBAT-LR (Ho et al 2023) can perform binning using Hi-C data and a set of assembled contigs. Proximity ligation also allows mobile elements to be associated with their respective host genomes, offering a unique advantage.…”
Section: Introductionmentioning
confidence: 99%